A Historical Review of Interactions, Exchanges, and Integration in Xinjiang and Reflections on Paths Toward Comprehensive Embedding - Huang, Xinning (Pacific International Journal, 2025)
Since 2012, China has placed significant emphasis on reinforcing common ground among all peoples at home, introducing new requirements to promote communication, exchange, and integration among the Chinese people. This paper examines the historical development of these processes from three perspectives: historical context, current significance, and future prospects. It explores the value and importance of communication, exchange, and integration within this region. Guided by the province’s governance policies in the new era, the paper investigates practical strategies to enhance these processes across five key areas: spatial integration, cultural exchange, economic cooperation, social cohesion, and psychological identification. This analysis aims to provide theoretical insights to support ongoing efforts to strengthen national unity in China.